Knowledge, attitudes, and practices of pharmacists toward over-the-counter medication use in Iraq: a nationwide cross-sectional study - AbdElrahman, Mohamed; D. Al-Rekabi, Mohammed; Ali Al-Oudah, Ghadah; M. Fayed, Aysam; Kamil Owadh, Hasanain (Frontiers in Pharmacology, 2025)
IntroductionOver-the-counter (OTC) medications play a vital role in global healthcare systems by offering accessible treatment options for minor ailments. However, the growing use of OTC drugs in Iraq raises concerns regarding pharmacists’ knowledge, safety perceptions, and dispensing practices.MethodsA nationwide cross-sectional survey was conducted among 529 licensed pharmacists from January to March 2025 across all major Iraqi regions. The questionnaire assessed demographics, familiarity with OTC drugs, safety attitudes, and dispensing behaviors.ResultsMost participants (95.4%) reported familiarity with OTC medications and frequent encounters with self-medicating patients, particularly in the Central and Southern regions. NSAIDs were the most commonly recommended OTC category (71.8%). Significant regional differences were observed in familiarity, frequency of self-medication, and safety perceptions (p = 0.0071, 0.00088, and 0.045, respectively). Pharmacists with less than 5 years of experience were more likely to report adverse drug reactions (p = 0.0332) and to inquire about patients’ OTC use (p = 0.1035). Overall, younger pharmacists and those practicing in the Kurdistan region demonstrated greater familiarity with OTC medicines, while neutral safety perceptions and practice in Southern Iraq were associated with lower familiarity.ConclusionIraqi pharmacists demonstrate generally strong awareness and proactive attitudes toward OTC medication use. Nonetheless, gaps remain in adverse reaction reporting and drug interaction recognition. Implementing standardized continuing education and structured OTC safety training could enhance practice consistency and promote safer self-medication behaviors nationwide.